THE EFFECT OF PERCEIVED BEHAVIORAL CONTROL, SUBJECTIVE NORMS, AND QUALITY OF TAX SERVICES ON TAXPAYER COMPLIANCE WITH TAX SANCTIONS AS A MODERATING VARIABLE - Duni, Duni; Kismanah, Imas; Rambe, Hikma Gustina; Supriyatno, Agus; Ranggala, Qadar (Dynamic Management Journal, 2025)
This study aims to examine the effects of Perceived Behavioral Control, Subjective Norms, and Quality of Tax Services on Taxpayer Compliance, with Tax Sanctions as a moderating variable. Using a quantitative approach, data were analyzed through multiple linear regression and moderation analysis using SPSS 25.0. The results indicate that Subjective Norms have a significant positive effect on taxpayer compliance, while Perceived Behavioral Control and Quality of Tax Services do not. Tax Sanctions strengthen the relationship between Subjective Norms and compliance, confirming their moderating role. However, Tax Sanctions do not moderate the effects of Perceived Behavioral Control or Quality of Tax Services on compliance. The findings highlight the importance of social influence and enforcement mechanisms in shaping taxpayer behavior. This study contributes to tax compliance literature by testing an extended Theory of Planned Behavior in a developing country context. It provides practical insights for tax authorities seeking to improve compliance through targeted policies and stronger sanction frameworks.